3D simulation analysis of hot machining of nickel alloy. (2020) - Kumar Parida, Asit; Maity, Kalipada; Brata Ghadei, Sataya
Abstract: FEM simulation software has been used in machining of Inconel-718 alloy to calculate the forces, temperature, stress and chip morphology in the present study. Johnson-cook material model and heat exchange window has used to perform flame heating turning operation. The simulations cutting forces decreased with the increased in heated temperature conditions. To validate simulation results, room and heat-assisted-machining experiment has been conducted and corresponding results has been compared